PRIORITY ISSUES FOR THE INTEGRATED MANAGEMENT OF THE WESTERN COASTAL ZONE OF THE GULF OF TONKIN - Thanh, Tran Duc (Vietnam Journal of Marine Science and Technology, 2009)
The priority issues for the integrated management of the Western coastal zone of the Gulf of Tonkin are identified based on the analysis of the data and doarments on the  natural  conditions  and  ecosystems,  the  state  and  tendency  of  the  environment  and resources; on the current status and the orientation of future socio - development; on the view point of the strategic, integrated, adaptative, and urgency nature of management issues; on the using methods of DPSIR model analysis (Drivers-Pressure-State-Impact-Response); on the spatial and temporal analysis; and on the development of matrix with weighting assessment. The analysis and selection of the priority have been performed for five management issues,  and  applied  for  the  management  models  of  4  different  spatial  levels  (the  western coastal  zone  of  Tonkin  Gulf,  the  coastal  region  of  the  Bac  bo,  the  coastal  sub-region  of Northeast Bac bo, and the coastal area of Haiphong) in three management periods: 2011 - 2015, 2016 - 2020, and 2021 - 2025. Beside of the coastal sub-region of Northeast Bac Bo, the estimation of priority issues were also made for the sub-regions of Thai Binh - Ninh Binh and Thanh Hoa – Quang Binh in the western coastal zone of the Gulf of Tonkin. The analysis shows that the management and rational use of natural resources are the first priority issue. The second priority is the management and prevention of pollution and environmental risks. These are priorities for all four spatial management levels, and for the entirely integrated management process. The natural and biodiversity conservation is placed at the forth for the western coastal zone of Tonkin Gulf and the coastal region of the Bac bo, but is the thirth priority for the coastal sub-region of Northeast Bac bo, and the coastal area of  Haiphong.  The  management  and  prevention  of  pollution  and  natural  disasters  are considered  as  the  thirth  priority  for  the  western  coastal  zone  of  Tonkin  Gulf,  the  coastal region of the Bac bo, but they are the forth priority for the coastal sub-region of Northeast Bac  bo,  and  the  coastal  area  of  Haiphong.  Last  but  not  least  is  the  issue  of  mitigation  of beneficiary  conflict.  However,  at  each  spatial  management  level  and  for  each  stage  of management process, one can always find out different priority management issues. In order to  succeessfully  implement  the  identified  priority  issues,  there  is  a  need  of  developing  and conducting  some  core  management  programs.  These  programs  will  go  throughout  three management  periods,  but  still  have  some  highlight  points  in  different  spatial  management levels, and each stage of the management process.